Development of Heyzine-Based Digibook to Enhance Students' Computational Thinking Skills - Taqwani, Ratna Amalia; Ratnaningsih, Nani; Lestari, Puji (PRISMA, 2025)
The purpose of this research is to develop a digital book about sequences and series using the Heyzine platform so that students of vocational high school (SMK) in tenth grade can improve their computational thinking abilities. This study employs a 4-dimensional model based on the Research and Development (R&D) approach: Specify, Create, Test, and Release. The study involves 10th-grade students in mathematics. Observation, interviews, expert validation sheets (media and content), user response surveys, and computational thinking skill assessments are some of the methods used to gather data. Compared to other platforms, Heyzine's interactive features, multimedia integration, and user-friendliness make it the best choice for this study because they encourage student engagement and computational thinking. Validation results show that the digibook is highly valid and suitable for classroom use. User responses were rated as “excellent.” The Effect Size (ES) test result was 1.23, indicating a strong impact of the intervention. Specifically, 69% of students were able to decompose problems into relevant data, and 69% successfully identified patterns to solve the tasks. Additionally, 54% identified key components while excluding irrelevant information, and 51% executed problem-solving steps sequentially and correctly. To sum up, the sequences and series digital textbook developed by Heyzine is a legitimate, interesting, and useful tool for enhancing students' computational thinking abilities in the context of vocational mathematics education.